Being bound in a fieldsite: Cross-cultural methodological notes on doing digital ethnography on TikTok - Abidin Crystal; Lee Jin (Cultural Science)
Digital ethnography requires attention to ethical processes, data complexity, and social interactions, particularly on emerging platforms like TikTok. This paper draws on our research in Australia and South Korea, examining the challenges of defining a ‘fieldsite’ within a platform that is both segmented and fluid. In Australia, issues of settler-colonialism and multiculturalism complicate the concept of an ‘Australian TikTok,’ necessitating a focus on minority voices. In contrast, South Korea’s cultural homogeneity and language create a more bounded data environment, yet the global rise of K-pop complicates data sampling as elements from Korean culture often lose their context. We discuss methodological insights for conducting digital ethnography on TikTok, considering researcher positionality and the influence of global research cultures.